A simplified prognostic index for chronic lymphocytic leukemia treated with ibrutinib: Results from a multicenter retrospective cohort study. (February 2020) - Gordon, Max J.; Sitlinger, Andrea; Salous, Tareq; Alqahtani, Hamood; Churnetski, Michael; Rivera, Xavier; Wisniewski, Paul; Cohen, Jonathon; Patel, Krish; Shadman, Mayzar; Choi, Michael; Hill, Brian; et al.
Highlights: The CLL international prognostic index (CLL-IPI) may not be applicable to CLL patients treated with targeted therapies. Especially with ibrutinib which demonstrates improved efficacy in patients with adverse features. We report a clinical tool which stratifies CLL treated with ibrutinib into low, intermediate and high risk groups.